Jamaica : Request for Stand By Arrangement and Cancellation of the Current Extended Arrangement Under the Extended Fund Facility-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Jamaica's Request for Stand By Arrangement (SBA) and Cancellation of the Current Extended Arrangement Under the Extended Fund Facility (EFF). Fiscal discipline and proactive debt management have helped reduce public debt by more than 25 percent of GDP since the start of the extended arrangement under the EFF. Macroeconomic stability is becoming entrenched as evidenced by low inflation, the buildup of foreign currency reserves, and a decline in the current account deficit. Important reforms are also being undertaken to unlock Jamaica's growth potential. In view of the country's recent track record and authorities' commitment to reforms and maintaining an open dialog with the IMF, the IMF staff supports the request for the precautionary SBA.